Targeting improved partial resistance using yield-loss response curves for foliar diseases of wheat - Shankar, Manisha; Reeves, Karyn; Bradley, Jason; Varischetti, Ryan; Platz, Greg; Snyman, Lisle; Hollaway, Grant; Cook, Melissa; Poole, Nick; Wylie, Tracey; Milgate, Andrew; Cao, Zhanglong; et al. (2020)
Key messages: Current resistance categories were well reflected in the yield responses observed for various wheat foliar diseases however, yield losses for particular resistance categories varied by disease and disease intensity. Disease expression increased with the susceptibility of varieties, resulting in correspondingly higher yield loss. Partially resistant varieties differed in the extent of their yield loss corresponding with lower disease expression. Partial resistance was effective in reducing losses from all diseases depending on the type and severity of disease and the yield potential. An online model has been developed so growers and consultants can make more informed decisions about variety and paddock selection by comparing yield responses to various resistance categories of individual diseases.